PENERAPAN SANKSI TINDAK PIDANA KHUSUS DALAM PEMILIHAN KEPALA DAERAH KABUPATEN INDRAMAYU : (Putusan Pengadilan Negeri Indramayu Nomor 335/Pid.Sus/2020/PN.Idm) - Murya, Adnan; Carto (Yustitia, 2022)
With the title "Normative Juridical Review of the Application of Special Criminal Sanctions in the Election of the Regional Head of Indramayu Regency (Decision of the Indramayu District Court Number 335/Pid.Sus/2020/Pn.Idm)" This study aims to identify and understand the regulation and application of the elements of neutrality. The Village Head and the consideration of the Panel of Judges in giving verdicts on the Crime of Election of the Regent and Deputy Regent of Indaramyu. This study uses the theory of the rule of law, legal certainty, justice, and expediency. The research method used is normative juridical law research, namely by collecting data by literature study by examining library materials or secondary legal materials.